Role of sST2 in prognostication and risk stratification in patients with heart failure - Thakre, Gaurav Pradip; Venkat, Manjunath Bagur; Sahoo, Bhabani Charan (International Journal of Research in Medical Sciences, 2017)
Background: sST2, an interleukin (IL)-1 receptor family member, has been identiﬁed as a novel biomarker for cardiac strain. Concentrations of sST2 have prognostic value and found to be predictive of the rate of mortality in the follow-up of patients after an acute heart failure episode. The present study aims to study relationship between serum sST2 levels along with prognosis and risk of mortality in heart failure patients. Methods: The Study was conducted in A.J. Institute of Medical Sciences, Mangalore, Karnataka, India with 56 heart failure patients in the duration of 1 year. sST2 level of each patient was taken on the day of admission then after one month, six months and one year. Results: Concentration of sST2 was consistently higher in 55.3% patients. Patients with lower values of ST2 levels were having less number of hospital admissions for heart failure symptoms (44.6%). The patients who were having high ST2 levels died due to cardiac events by the end of one month, six months and one year were 7.1%, 11.5% and 13% respectively (p<0.001) which was highly significant. Overall mortality with the patients who were having higher ST2 levels was 28.5% (p<0.001 HS). Conclusions: Elevated sST2 levels are predictive of cardiac events in patients with heart failure and provide complementary information about prognostication and risk stratification of patient. Serial monitoring of sST2 will aid in clinical decision making.